Pengaruh Pemasaran Digital Dan Kualitas Produk Terhadap Loyalitas Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pembelian Produk Fashion “Second Kita” - Fransisca, Anatasya Dea; Wantara, Pribanus (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to analyze: (1) The influence of digital marketing on customer loyalty when purchasing "Second Kita" fashion products, (2) The influence of product quality on customer loyalty when purchasing "Second Kita" fashion products, (3) The influence of customer satisfaction on loyalty customers when purchasing “Second Kita” fashion products, (4) The influence of digital marketing on customer satisfaction when purchasing “Second Kita” fashion products, (5) The influence of product quality on customer satisfaction when purchasing “Second Kita” fashion products, (6) the influence digital marketing on loyalty through customer satisfaction when purchasing "Second Kita" fashion products, (7) the influence of product quality on loyalty through customer satisfaction when purchasing "Second Kita" fashion products.  The type of research used is quantitative, with "Second Kita" customers as research respondents who have made a purchase at least once. The analytical method used in this research uses Partial Least Square (PLS) 4 with outer model and inner model coefficient tests and hypothesis testing. The results of this research show that digital marketing does not have a significant influence on customer loyalty or customer satisfaction. On the other hand, product quality has a significant effect on customer loyalty and customer satisfaction. Customer satisfaction also has a significant effect on customer loyalty. Apart from that, digital marketing does not have a significant effect on customer loyalty through customer satisfaction, while product quality has a significant effect.